3D kinematic analysis of two different roundhouse kick in elite karate players - Paydar, A.; Golmoghani Zadeh, N.; Zorba, E.; Korkusuz, F. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The main objective of this study was to determine differences, if any, in three-dimensional (3D) kinematic characteristics of the two kind of roundhouse kick (Giako and kizami mawashi geri), elite level karate players. Specifically, the kinematic variables related to the displacement, linear velocity and acceleration of the lower body segments, translational leg acceleration and vertical ground reaction force generated by karate players were analyzed. Methods: The subject of this study composed of 21 elite level amateur male karate players. Ages of the subjects ranged from 20 to 26 years old. All subjects executed two kick. The motions were captured with Phases pace real time optical tracking system with 8 high speed cameras at 240 fps. Then, the motions captured were analyzed to quantify the kinematic factors associated with each kick. Results: The results showed that the kizami mawashi geri generated larger linear velocity compared to the giako mawashi geri. Similarly, the kizami mawashi geri generated larger linear acceleration compared to the giako mawashi geri. Moreover, the giako mawashi geri generated larger transitional leg acceleration compared to the kizami mawashi geri. Discussion: As a conclusion, the results for all kinematic variables demonstrated that the type of kick was the major determinant of the magnitude of each factor studied. Moreover, the technique employed can significantly affect the resulting displacement, linear velocity and acceleration, and transitional leg acceleration of the kick.